Code of honor (Journal of Philosophy Culture and Political Science, 2018)
This article analyzes the creativity Roses Mukhanova based on her stories and drama «I’m under the roof.» Their opinion we titled «Code of Honor», because all the creativity is Roses Mukhanova, permeated the advanced thought , high pretension and deep knowledge of the ethical ,cultural, psychological, spiritual problems of the Kazakh people . Author its bright, colorful language has managed to convey to the readers the simple things. Each Roses works about problems that occur, each person and manifestations of human, qualities measurements of human life. Another important feature of Roses Mukhanova – deep knowledge of the natural features of the Kazakh language knowledge words .This probably explains what ‘s short stories ,but concise. No those unnecessary, endless, bored details that often interfere with the reader. Each word in its place, clearly fulfills its function. Key words: Philosophical prose, humanity, conscience, honor, human destiny, love , human dignity, human existence .